1st make 2x-1=y
substitude 2x-1=y into -2x+3y=5
-2x+3(2x-1)=5
-2x+6x-3-5=0
4x-8=0
4x=8
x=2
replace x=2 into 2x-y=1
2(2)-y-1=0
3-y=0
y=3
2007-06-03 15:05:32
·
answer #1
·
answered by X0n 1
·
0⤊
0⤋
Your teacher probably wants to see something like this:
To do it by addition, write them one above the other:
2x - y = 1
+( -2x + 3y = 5)
---------------------
Now, add the terms as if you were doing long addition:
2x - 2x = 0; -y + 3y = 2y; 1 + 5 = 6.
This gives you:
0 + 2y = 6
Solving, y=3. Then, substituting y=3 in either of the given equations gives x = 2.
And, always check your work.
2(2) - 3 = 1 ?? Yes
-2(2) + 3(3) = 5 ?? Yes.
2007-06-03 22:16:47
·
answer #2
·
answered by Mr Placid 7
·
0⤊
0⤋
2x - y + -2x + 3y = 1 + 5 : add the equations
2y = 6 : simplify
y = 3 : divide by 2
2x - 3 = 1 : plug y value into first equation
2x = 4 : add 3 to both sides
x = 2 : divide by 2
-2(2) + 3(3) = 5 ?
-4 + 9 = 5 so it checks
2007-06-03 23:18:40
·
answer #3
·
answered by Don E Knows 6
·
0⤊
0⤋
2x-y=1
-2x+3y=5
2y=6
y=3
2x-3=1
2x=4
x=2
2007-06-03 23:46:51
·
answer #4
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
(3/2,2)
2007-06-03 22:04:14
·
answer #5
·
answered by Yehudiit 4
·
0⤊
0⤋